2017
DOI: 10.5604/01.3001.0011.6465
|View full text |Cite
|
Sign up to set email alerts
|

Provided Leadership and Selected Outcomes of Trainings in Public Organizations

Abstract: Trainings as well as their impact on employability and employees’ performance have been the subject of interest of theoreticians and practitioners of management for a long time. However, according to the literature study, the outcomes of employees’ trainings also depend on the applied style of leadership as well as on the quality of relationships between supervisors and subordinates. This paper tries to answer the question: what are the relationships between transformational leadership, the quality of supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Regarding context, and work contexts particularly, researchers have studied the relationship between leadership and employability in both non-profit and for-profit organizations. Most of the studies assessed in the current study (5), were conducted in education contexts, such as universities (Camps and Rodríguez, 2011; Van der Heijden and Spurk, 2019), higher vocational education institutions (Bhattacharya and Neelam, 2018;Gustari and Widodo, 2020), and primary schools (Struzyna and Marzec, 2017), followed closely by 3 studies conducted in small-and medium-sized enterprises (SMEs) (Bozionelos et al, 2016;Stoffers et al, 2019;Epitropaki et al, 2021). Building (Van der Heijden and Bakker, 2011; Van der Heijde and Van der Heijden, 2014), and healthcare organizations, such as nonacademic hospitals (Van Harten et al, 2016), acute-care hospitals (Matsuo, 2022), and public healthcare units (Struzyna and Marzec, 2017), have been assessed in several studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding context, and work contexts particularly, researchers have studied the relationship between leadership and employability in both non-profit and for-profit organizations. Most of the studies assessed in the current study (5), were conducted in education contexts, such as universities (Camps and Rodríguez, 2011; Van der Heijden and Spurk, 2019), higher vocational education institutions (Bhattacharya and Neelam, 2018;Gustari and Widodo, 2020), and primary schools (Struzyna and Marzec, 2017), followed closely by 3 studies conducted in small-and medium-sized enterprises (SMEs) (Bozionelos et al, 2016;Stoffers et al, 2019;Epitropaki et al, 2021). Building (Van der Heijden and Bakker, 2011; Van der Heijde and Van der Heijden, 2014), and healthcare organizations, such as nonacademic hospitals (Van Harten et al, 2016), acute-care hospitals (Matsuo, 2022), and public healthcare units (Struzyna and Marzec, 2017), have been assessed in several studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Data were retrieved from the Web of Science database using the search string: topic "employability," document type "articles," language "English" OR "Dutch," and publication years . (Struzyna and Marzec, 2017), information and communication technology (Wang et al, 2019), food and beverage (Chughtai, 2019), automotive (Böttcher et al, 2018), insurance (Park, 2020), and mixed-industry (e.g., construction, manufacturing, finance, insurance, and communication; Yizhong et al, 2019) organizations have been assessed.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted in the Netherlands indicated that training has a positive impact not only on the employability of employee, but also on their career advancement (Groot and Maasen van den Brink, 2000). In addition, research conducted in various industries in Malaysia found that training enhances both the internal and external employability of employees (Juhdi et al, 2010), some research in public sector organizations shows that formal on-the-job learning supported by organization leaders has a positive impact on employability (Nelissen et al, 2017;Strużyna and Marzec, 2017).Thus, it can be assumed that:…”
Section: Training and Development As A Basis For The Employability Enhancementmentioning
confidence: 99%
“…The results of quantitative research conducted within the framework of the project were also presented in the papers byStrużyna and Marzec (2017) andMarzec (2019) in which a subset of the total sample and variables presented in the paper was only utilized.…”
mentioning
confidence: 99%